Tuning the Physicochemical, Structural, and Antimicrobial Attributes of Whey-Based Poly (L-Lactic Acid) (PLLA) Films by Chitosan Nanoparticles - Garavand, Farhad; Rouhi, Milad; Jafarzadeh, Shima; Khodaei, Diako; Cacciotti, Ilaria; Zargar, Masoumeh; Razavi, Seyed Hadi (Frontiers in Nutrition, 2022)
Recently, the research and innovation to produce raw materials from microbial processes has gained much attention due to their economic and environmental impacts. Lactic acid is a very important microbial product due to its wide application in the food, pharmaceutical, cosmetic, and chemical industries. In the current study, poly-L-lactic acid (PLLA) was produced by the ring opening polymerization (ROP) technique of L-lactic acid recovered from whey fermentation, and was used for the production of nanocomposites films reinforced with chitosan nanoparticles (CNPs) (average diameter ca. 100-200 nm). Three different CNPs concentrations, namely 1, 3 and 5 % w/w, were tested, and their influence on the physical, mechanical, thermal, antibacterial and structural attributes of PLLA film was assessed. The results showed that the addition of CNPs up to 3% caused a significant improvement in water vapour permeability, appearance, tensile strength and elongation at break. The antibacterial properties of nanocomposites followed a dose-depended pattern as a result of CNPs addition. Therefore, the best inhibitory effects on Escherichia coli and Staphylococcus aureus was made by the addition of 5% of CNPs and lower dosages slightly affected the growth of pathogens or didn’t cause any inhibitory effects (in 1% of CNPs). It can be concluded that the incorporation of CNPs into the PLLA matrix allows to improve the polymer structural, thermal, physical, mechanical and antibacterial properties of the polymer, generating promising systems for food packaging and biomedical applications.